Sophia, Mary and the Eternal Feminine in Pierre Teilhard de Chardin and Sergei Bulgakov - Deane-Drummond, Celia (Journal for the study of religion, nature and culture, 2005)
This paper explores the relationship between Mary, Sophia and the Eternal Feminine in the writings of Pierre Teilhard de Chardin and Sergei Bulgakov. It argues that Teilhard’s poem to the Eternal Feminine is a meditation on the Virgin Mary and reflected his own dedication to her. While Teilhard’s attention to wisdom is veiled and somewhat restricted, it flowers in the theology of Bulgakov, who finds in Mary the expression of perfected creaturely Sophia. Both authors have a high place for Mary and her cosmic significance, though this is muted somewhat in Teilhard’s account by his strong attention to cosmic Christology. While Mary and nature have long been associated in the Christian tradition, a Sophianic interpretation of her importance allows for an ecological reading of Mary’s significance that goes beyond the interpretation of both Teilhard and Bulgakov.